Studi Perencanaan dan Pengembangan Objek Wisata Danau (Studi Kasus Situ Ciburuy) - Rieke Sri Rizki Asti Karini; Rachmat Astiana (Tourism Scientific Journal, 2022)
This study aims to determine the actual conditions (physical and non-physical) aspects of lake tourism development, to know the policy analysis of Situ Ciburuy tourism object development as a lake tourism development planning strategy, to know Situ Ciburuy tourism activities and market analysis of Situ Ciburuy tourism products as a lake tourism development planning strategy and know the planning strategy for sustainable tourism development in the context of developing lake tourism. The research is qualitative in nature, using primary data through observation, interviews and secondary questionnaires through documents and scientific journals. The analytical method used is SWOT analysis which identifies various factors to formulate a strategy. Based on the SWOT analysis of internal and external strategic factors. Situ Ciburuy internally has a strength value that is greater than its weakness, while externally it has an opportunity value that is greater than its threats. strength factors maximize the utilization of all opportunities. The recommended strategy is making a master plan for the Situ Ciburuy area as a guideline for spatial planning or land allotment and collaborating with investors in increasing the quality and quantity of objects and tourist attractions in the Situ Ciburuy area so as to increase the number of visitors in the future.